Identification of Coastal Damage Along the Coast of Riau - Muhardi Muhardi; Aminaton Marto; Manyuk Fauzi; Bambang Sujatmoko; Malik Habibillah; Mohd Syarwan (Lowland Technology International, 2021)
Riau Province has a broad coastline along its territory and it directly meeet the Malacca Strait. Costal, marine and island areas in Riau Province are currently of serious concern due to problems such as the reduction and addition of coastline (abrasion, erosion and sedimentation). This research aims to examine the extent of coastal damage that has occurred so far in reducing abrasion and priorit determination to the beach to be handled based on the level of coastal damage associated with the level of coastal importance. The areas that have the highest level of weighting (priority level A and B) are coastal areas in Bengkalis Regency (Api-api Beach, Tanjung Leban Beach, Muntai Beach and Senekip Beach), Dumai City (Purnama Beach and Bahtera Alam Beach) adn Indragiri Hilir Regency (Kuala Enok Beach). Meanwhile in Meranti Regency all the beaches reviewed have a high weighting value.